Menakar Lembaga Antikorupsi: Studi Peninjauan Kinerja Komisi Pemberantasan Korupsi - Suyatmiko, Wawan Heru; Nicola, Alvin (Integritas: Jurnal Antikorupsi, 2019)
There is no universal standard in establishing and operating an ideal anti-corruption institution (ACA). Since 2013, Transparency International has developed a measurement tool that can capture the effectiveness of ACAâ€™s performance in accordance with UNCAC’s mandate and the Jakarta Principles. One of the main aspects is whether the ACA is in a supportive environment or is in a policy situation that impedes the implementation of anti-corruption laws. This study specifically seeks to review the strengths and weaknesses of Indonesian ACA, the Corruption Eradication Commission (KPK), based on TIâ€™s measurement tools above, through 6 dimensions spread across 50 indicators over the 2016-2019 period. The study found that the KPK had strong and supportive environmental factors, both internally and externally, but has some notable exceptions in the aspect of independence. ACAâ€™s performance measurement, whether carried out internally or externally, is significant to strengthen ACA independence and law enforcement in the long run.